Cranial osteology of Arctognathus curvimola, a short‐snouted gorgonopsian from the Late Permian of South Africa. (7th October 2014) - Kammerer, Christian F.; Angielczyk, Kenneth
Abstract Gorgonopsia is one of the major clades of nonmammalian therapsids and includes the dominant vertebrate predators of the Late Permian. Unfortunately, gorgonopsian taxonomy is extremely problematic, due in large part to the lack of thorough descriptions and clear differential diagnoses for most nominal species. Here, the South African gorgonopsian species Arctognathus curvimola is redescribed based on a well‐preserved skull. Autapomorphies identified for A. curvimola include a characteristic curvature to the alveolar margin of the snout, extremely reduced lacrimal, lengthy upper postcanine tooth row and a unique vomerine morphology. The nominal gorgonopsian species Arctognathoides breviceps and Lycaenodontoides bathyrhinus are considered junior synonyms of A. curvimola. Other referred species of Arctognathus (A. whaitsi, A.? cookei and A.? nasuta) share no unique characters with A. curvimola and are removed from the genus; their generic placement is uncertain at present. Previous reports of Arctognathus from Tanzania and the Middle Permian of South Africa are not referable to this taxon. At present, definitive specimens of A. curvimola are restricted to the Upper Permian Cistecephalus and Dicynodon assemblage zones of South Africa.